Life lessons - Nitschke, Jonathan R. (Beilstein Journal of Organic Chemistry, 2015)
Reminiscing about his younger self: “I mean I can’t very well just 86 [in American slang, to “86” is to eject, remove, or discard someone or something, J.R.N.] this guy from my life. On the other hand, if through some as yet undeveloped technology I were to run into him today, how comfortable would I feel about lending him money, or for that matter even stepping down the street to have a beer and talk over old times?” ― Thomas Pynchon, Slow Learner
Keywords: autobiography; host–guest; self-assembly; supramolecular